Coracoclavicular ligament augmentation at clavicle distal-third fracture treatment - Karslioglu, Bulent; Uzun, Metin; Dedeoglu, Suleyman Semih; Imren, Yunus; Keskin, Ahmet (ScienceRise: Medical Science, 2021)
The aim: type 2B clavicle fractures with conoid ligament rupture are considered unstable. Although surgical treatment is recommended as the standard treatment modality for type 2B fractures, there is no consensus about the type of operative treatment. We aimed to evaluate results of surgical treatment with an anatomical distal clavicle plate using CC ligament augmentation. Materials and methods: 15 patients that diagnosed with distal clavicle fractures, who underwent surgery for unstable type 2 fractures. The average patient age was 38 years (range 24–52 years). All patients were male; the right clavicle was injured in 10 patients whereas the left clavicle was injured in 5 cases. Surgical treatment was done with a distal clavicle anatomic locked plate augmentation (ZipTight™) at all cases. The mean follow-up period was 24 months (range, 12–40 months). Results: bony union was achieved at a mean follow-up of 8 weeks (range 6-10 weeks). The mean Constant score was 97 (range, 92–100). There were no complications or no need to second operation. All patients achieved satisfactory full range of shoulder motion. Hardware removal was performed for prominence in one case after the union was completed. Conclusion: the augmented technique reported here, provides early motion, increased stability and anatomic healing compared to other conventional options. We recommend augmentative CC ligament repair techniques over the distal locking anatomic plate for type 2 fractures